Eleutherococcus Species Cultivated in Europe: A New Source of Compounds with Antiacetylcholinesterase, Antihyaluronidase, Anti-DPPH, and Cytotoxic Activities. (10th March 2019) - Adamczyk, Kuba; Olech, Marta; Abramek, Jagoda; Pietrzak, Wioleta; Kuźniewski, Rafał; Bogucka-Kocka, Anna; Nowak, Renata; Ptaszyńska, Aneta A.; Rapacka-Gackowska, Alina; Skalski, Tomasz; Strzemski, Maciej; Sowa, Ireneusz; et al.
Abstract : Secondary metabolites of the roots of Eleutherococcus spp. cultivated in Poland, or the bioactivity, are not fully known. The 75% methanol extracts of five Eleutherococcus spp. ( E. senticosus, E. divaricatus, E. sessiliflorus, E. gracilistylus, and E. henryi ) were examined for the content of polyphenols and phenolic acids as well as for antiacetylcholinesterase, antihyaluronidase, anti-DPPH ∗, and cytotoxic activities. The richest in polyphenols were the roots of E. henryi (10.4 mg/g DW), while in flavonoids the roots of E. divaricatus (6.5 mg/g DW). The richest in phenolic acids occurred the roots of E. henryi [protocatechuic acid (1865 μ g/g DE), caffeic acid (244 μ g/g DE), and p -coumaric and ferulic acids (55 μ g/g DE)]. The highest inhibition of AChE was observed for E. gracilistylus and E. sessiliflorus (32%), at the concentration of 100 μ g/0.19 mL of the reaction mixture, while that of Hyal for the roots of E. henryi (40.7%), at the concentration of 100 μ g/0.16 mL of the reaction mixture. Among five species tested, the E. henryi extract exhibited the strongest HL-60 cell line growth's inhibition (IC50 270 μ g/mL). The extracts reduced DPPH ∗ in a time-dependent mode, at the concentration of 0.8 mg/mL. After 90 min from 14.7 to 26.2%, DPPH ∗ was reduced. A phytochemical composition and activity of the Eleutherococcus species, cultivated in Poland, are still under research; however, on the basis of the results obtained, it may be concluded that they may become a source of phytochemicals and be useful for Europe's citizens.